Catalytic behavior of ABO(3) perovskites in the oxidative coupling of methane - Sim, Yujin; Kwon, Dahye; An, Suna; Ha, Jeong-Myeong; Oh, Tae-Sik; Jung, Ji Chul (ELSEVIER, 2020)
Herein, we attempted to identify the active sites behavior of perovskite catalysts in the oxidative coupling of methane (OCM) reaction, using ten types of ABO(3) perovskite catalysts with different structural properties according to their A and B site elements. The results showed that the catalyst surface lattice oxygen species are responsible for the selective conversion of methane. In particular, surface lattice oxygen species with moderate binding energies selectively catalyzed the OCM to produce C-2 hydrocarbons. The surface oxygen vacancies, resulting from the reaction of lattice oxygen and CH4, were refilled with adsorbed surface oxygen and bulk lattice oxygen species. This oxygen cycle was closely related to the oxygen ion conductivity of perovskites, which could be determined based on their structural factors, such as the tolerance factor and the specific free volume. Accordingly, a facile oxygen cycle resulted in a high CH4 conversion during this reaction. Finally, we concluded that the lattice oxygen properties and the oxygen ion conductivity of perovskite catalysts are key factors in determining the catalytic activity and should, therefore, be precisely controlled for the systematic design of efficient OCM catalysts.
Keywords: OXIDE-ION CONDUCTIVITY; NATURAL-GAS; OXYGEN; CONVERSION; MODEL; NONSTOICHIOMETRY; MN-NA2WO4/SIO2; SUBSTITUTION; MAGNESIUM; MEMBRANE